2019
DOI: 10.1002/admi.201802058
|View full text |Cite
|
Sign up to set email alerts
|

Universal Work Function of Metal Oxides Exposed to Air

Abstract: Metal oxides are the cornerstone of thin‐film electronics, a multibillion dollar industry, because they possess a wide variety of optoelectronic properties, exhibit novel functionalities, and can typically be fabricated from cheap, nontoxic raw materials. However, for thin‐film electronics to achieve further market penetration, it is necessary to replace expensive vacuum‐based fabrication processes with low‐cost, large‐scale solution‐based methods. Here, the influence of exposure to air on the band energies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…From secondary electron cutoff of the low‐intensity X‐ray photoelectron spectroscopy (LIXPS) spectra ( Figure A), the work function of the [FeFe] modified Si (Si‐[FeFe]) was determined to be approximately equal to that of an oxide‐free, freshly ion‐sputtered bare Si wafer. This result demonstrates that covalent [FeFe] modification is capable of inhibiting oxide growth maintaining the work function of Si after exposure to air for 300 h. The work function of bare Si is 0.75 eV more positive than that of the treated surface due to native oxide growth, [ 38 ] demonstrating that the modified surface possesses favorable electronic properties for more efficient charge transfer compared to the bare Si surface. In solution phase, the flat band potential can be determined by an approximation of the valence band edge potential, [ 39 ] where a shift in flat band potential reflects changes in the valance and conduction band positions.…”
Section: Resultsmentioning
confidence: 91%
“…From secondary electron cutoff of the low‐intensity X‐ray photoelectron spectroscopy (LIXPS) spectra ( Figure A), the work function of the [FeFe] modified Si (Si‐[FeFe]) was determined to be approximately equal to that of an oxide‐free, freshly ion‐sputtered bare Si wafer. This result demonstrates that covalent [FeFe] modification is capable of inhibiting oxide growth maintaining the work function of Si after exposure to air for 300 h. The work function of bare Si is 0.75 eV more positive than that of the treated surface due to native oxide growth, [ 38 ] demonstrating that the modified surface possesses favorable electronic properties for more efficient charge transfer compared to the bare Si surface. In solution phase, the flat band potential can be determined by an approximation of the valence band edge potential, [ 39 ] where a shift in flat band potential reflects changes in the valance and conduction band positions.…”
Section: Resultsmentioning
confidence: 91%
“…The results presented in Figure 8 confirm that the same applies to Fe as well, as was already suggested in Huber and Kirk. 36 The influence of exposure to air on the band energies of metal oxides was also investigated in Rietwyk et al 37 and universal reduction in the work function was observed across 18 oxides. This effect arises from charge transfer events with the ubiquitous water layer that forms on surfaces in air.…”
Section: Near-zero Landing Energies In Semmentioning
confidence: 99%
“…80,81 The oxide layer on top of the metal electrode will be hydroxyl terminated, followed by a physisorbed layer of water, hydrocarbons and other small molecules when exposure to air, which will form a dipole moment pointing away from the surface and decrease the work function significantly. 82 In the case of non-reactive metals or the reactive metals in the inert atmosphere, there will be a physisorption of heteroatoms and small molecules directly on the metal surface and the work function is reduced by the push-back effect. Even if the electrode is made in-situ, its surface may also be slightly contaminated and/or oxidized due to the higher pressure used during the deposition process (> 10 -7 mbar).…”
Section: Energy Level Alignmentmentioning
confidence: 99%